In Silico Study on the Effect of Heliannuol A, B, C, D, E Compounds of Sunflower (Helianthus annuus L.) on Dual PI3K/mTOR (5OQ4) Enzyme - Roihatul Mutiah; Yen Yen Ari Indrawijaya; Tanaya Jati Dharma; Jamilah Damaiyanti (Majalah Obat Tradisional, 2021)
Heliannuol is a sesquiterpene that has a benzoxepine ring, oxepin. Many derivatives of benzoxepine compounds show anticancer activity by inhibiting the phosphoinositide 3-kinase (PI3K) enzyme. These enzymes play a role in cell proliferation and growth. The study aims to predict the physicochemical properties using Lipinski’s Rule of Five parameters on phosphoinositide 3- kinase (PI3K/Mtor; PDB 5OQ4) enzyme and the toxicity of Heliannuol A, B, C, D, E compounds. The process uses the pkCSM online tool. The validation of receptor 5OQ4 is done using the value parameter RMSD < 2 (Å). Protox online tool dan pkCSM online tool is employed to predict the toxicity using parameter LD50, skin sensitization, Ames toxicity, hepatotoxicity, and toxicity class. The interaction of ligan and enzyme is tested using Molegro Virtual Docker 6.0. Heliannoul A, B, C, D, E compounds fulfill Lipinski’s Rule of Five. The receptor 5OQ4 is known valid using the value of RMSD 0,923 (Å). Heliannuol A, B, C, D, E compounds inhibit Dual PI3K / mTOR enzyme less than Bimiralisib. As a result of the toxicity test of compounds Helliannouls A, B, C, E, and Bimiralisib compounds are included in class 4, while Helliannouls D compounds are included in class 5.